per Pertunjukan kolosal "Pemberontakan PETA Blitar" dalam rangka hari pemberontakan PETA di Kota Blitar tahun 2024: Pertunjukan Kolosal Pemberontakan PETA Blitar - Selviana, Else (Solah, 2025)
The presence of the Colossal Drama Performance "PETA Rebellion Blitar" in the Commemoration of PETA Rebellion Day in Blitar City in 2024, is a product of performing arts creativity that not only has an attraction to the form of its appearance, but also has a contribution or has a function for the life of the people of Blitar City. The Colossal Drama "Pemberontakan PETA Blitar" is an interesting material object to be researched, so that the results can become a meaningful scientific document for the continuity of performing arts life. Therefore, researchers are interested in examining the form and function of the colossal drama performance "Pembentokan PETA Blitar" in Commemoration of PETA Rebellion Day in Blitar City in 2024. The research, which raised the material object of the Colossal Drama Performance "Pemberontakan PETA Blitar" in Commemoration of PETA Rebellion Day in Blitar City in 2024, was conducted using a qualitative approach with data collection techniques through observation, interviews, literature studies, and documentation studies. Data analysis was carried out through stages: Data collection, analysis and presentation of results. The results showed: : (1) The function of the performance of "Pemberontakan PETA Blitar" 2024 is divided into two types, namely primary and secondary functions. The primary function of this performance is as a medium for aesthetic presentation and emotional experience, while the secondary function is as a means of education, social integration, and preservation of local culture and identity.